2018
DOI: 10.1002/jcb.27616
|View full text |Cite
|
Sign up to set email alerts
|

Improvement of membranous nephropathy by inhibition of miR‐193a to affect podocytosis via targeting WT1

Abstract: The objective of this paper was to explore the role and molecular mechanism of miR-193a in membranous nephropathy (MN). Experimental rats and podocytes were randomly divided into four groups: control, MN, miR-NC, and miR-193a inhibitor groups. The relative mRNA level of miR-193a was determined. The mRNA level and protein expression of PODXL, NPHS1, and Notch1 were determined by real-time polymerase chain reaction (RT-PCR) and Western blot analysis, respectively. The mRNA level and protein expression of WT1 in … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1
1

Citation Types

1
14
0

Year Published

2021
2021
2023
2023

Publication Types

Select...
7

Relationship

0
7

Authors

Journals

citations
Cited by 16 publications
(15 citation statements)
references
References 31 publications
1
14
0
Order By: Relevance
“…30 Increased apoptosis in MN was another hallmark observed in our protein signature data and is consistent with glomerular injury that results in cell death and loss of podocytes. 31,32 In contrast, MCD generally displayed a different immune profile and reduced cell death but enhanced vascular functions compared with MN. For example, several proteins involved in adaptive immunity were dysregulated in MCD, including CD40LG, CSF1, TNFRSF17, CCL21, and STAT1/3, in keeping with the proposed disease pathogenesis that involves T and B lymphocytes.…”
Section: Discussionmentioning
confidence: 98%
“…30 Increased apoptosis in MN was another hallmark observed in our protein signature data and is consistent with glomerular injury that results in cell death and loss of podocytes. 31,32 In contrast, MCD generally displayed a different immune profile and reduced cell death but enhanced vascular functions compared with MN. For example, several proteins involved in adaptive immunity were dysregulated in MCD, including CD40LG, CSF1, TNFRSF17, CCL21, and STAT1/3, in keeping with the proposed disease pathogenesis that involves T and B lymphocytes.…”
Section: Discussionmentioning
confidence: 98%
“…16 A recent study demonstrated that the phenotypic change of podocytes might also be induced by the deletion of WT1, 27 which is required for maintaining the differentiated phenotype during podocyte injury in proteinuric kidney diseases, such as diabetic nephropathy and MN. 28,29 Interestingly, the inhibition of FH activity and the subsequent accumulation of fumarate have been reported to trigger the change of phenotypic profile through the mechanism by which fumarate induces ROS by modifying glutathione metabolism or ROS-related-miRNAs. 21,22,30 In the present study, we demonstrated that the podocytes in the milieu of PLA2R-associated MN lose their epithelial and differentiation markers accompanied by the acquisition of mesenchymal features.…”
Section: Discussionmentioning
confidence: 99%
“…For example, miR-193a-5p expression levels are downregulated in numerous types of cancer, including colon cancer, non-small cell lung cancer, human endometrioid endometrial adenocarcinoma and prostate cancer, which has been reported to be associated with tumor progression (18)(19)(20)26,27). A previous study also reported an improvement to membranous nephropathy following miR-193a inhibition, which affected podocytosis by targeting WT1 transcription factor (WT1) (28). Jin et al (29) demonstrated that miR-193a-5p exerted a tumor-suppressive role in glioblastoma via modulating NOVA alternative splicing regulator 1.…”
Section: Discussionmentioning
confidence: 99%